Mitogen-activated Protein Kinase Phosphatase-2 Deletion Impairs Synaptic Plasticity And Hippocampal-Dependent Memory - Nor Zaihana Abdul Rahman; Sam M. Greenwood; Ros R. Brett; Kyoko Tossell; Mark A. Ungless; Robin Plevin; Trevor J. Bushell (Society for Neuroscience, 2024)
Mitogen-activated protein kinases (MAPKs) regulate brain function and their dysfunction is implicated in a number of brain disorders, including Alzheimer’s disease. Thus, there is great interest in understanding the signaling systems that control MAPK function. One family of proteins that contribute to this process, the mitogen-activated protein kinase phosphatases (MKPs), directly inactivate MAPKs through dephosphorylation. Recent studies have identified novel functions of MKPs in development, the immune system, and cancer. However, a significant gap in our knowledge remains in relation to their role in brain functioning. Here, using transgenic mice where the Dusp4 gene encoding MKP-2 has been knocked out (MKP-2 / mice), we show that long-term potentiation is impaired in MKP-2 / mice compared with MKP-2 / controls whereas neuronal excitability, evoked synaptic transmission, and paired-pulse facilitation remain unaltered. Furthermore, spontaneous EPSC (sEPSC) frequency was increased in acute slices and primary hippocampal cultures prepared from MKP-2 / mice with no effect on EPSC amplitude observed. An increase in synapse number was evident in primary hippocampal cultures, which may account for the increase in sEPSC frequency. In addition, no change in ERK activity was detected in both brain tissue and primary hippocampal cultures, suggesting that the effects of MKP-2 deletion were MAPK independent. Consistent with these alterations in hippocampal function, MKP-2 / mice show deficits in spatial reference and working memory when investigated using the Morris water maze. These data show that MKP-2 plays a role in regulating hippocampal function and that this effect may be independent of MAPK signaling.